'Brandspeak': Metaphors and the rhetorical construction of internal branding. (January 2018) - Müller, Monika
Metaphorical phrases appear frequently in practitioner and academic texts on internal branding and depict employees as 'brand ambassadors' who 'embody the brand' and ultimately turn into 'living brands'. In this article, I examine how these metaphorical phrases rhetorically construct the concept of internal branding and thereby also impact our thoughts on organizations, employees and their relationships to one another. The findings show that complex metaphorical phrases provide linguistic framing for internal branding and simultaneously convey conflicting messages to different stakeholder groups. These metaphors describe internal branding as empowering employees to be autonomous and encouraging them to take control over the brand, whereas connotations paint a picture of employees being controlled by the brand. This article contributes to studies on internal branding, branding more generally, and on language in critical management studies by highlighting that internal branding metaphors point to a hidden value system that values brands higher than employees. This value system reflects tensions around the increasing financial value of brands and increasingly precarious working conditions.